2019
DOI: 10.2478/pcssr-2019-0025
|View full text |Cite
|
Sign up to set email alerts
|

Life Skill Development and Transfer beyond Sport

Abstract: The aim of this research was to investigate the current life skills education programs offered by the Australian Football League (AFL) for elite footballers in order to determine the retention of life skill knowledge and transfer beyond sport. Life skill education in sport is an increasing phenomenon. Life skills sport programs are capable of delivering positive outcomes when nurtured through a deliberately designed curriculum and purposeful teaching strategies. However, it is not known how life skills are lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…27 Similarly, although life skill development opportunities are offered in many Australian sporting systems, one study in Australian Rules Football reported failing to connect skills learnt in these programmes to life after sport. 28 In contrast, qualitative interviews of individuals who had participated in youth soccer academies suggest that talent development systems can provide transferable life skills that prepare players for life beyond sport. 29 Regarding ethical behaviour, one study indicates that youth soccer athletes at higher competitive levels may demonstrate lower moral judgement and moral intention than athletes at lower competitive levels.…”
Section: Physical Healthmentioning
confidence: 99%
“…27 Similarly, although life skill development opportunities are offered in many Australian sporting systems, one study in Australian Rules Football reported failing to connect skills learnt in these programmes to life after sport. 28 In contrast, qualitative interviews of individuals who had participated in youth soccer academies suggest that talent development systems can provide transferable life skills that prepare players for life beyond sport. 29 Regarding ethical behaviour, one study indicates that youth soccer athletes at higher competitive levels may demonstrate lower moral judgement and moral intention than athletes at lower competitive levels.…”
Section: Physical Healthmentioning
confidence: 99%